Atrial functional mitral regurgitation: prevalence, characteristics and outcomes from the National Echo Database of Australia. Issue 1 (15th February 2023) - Moonen, Avalon; Ng, Martin K C; Playford, David; Strange, Geoff; Scalia, Gregory M; Celermajer, David S
Abstract : Aims: Atrial functional mitral regurgitation (AFMR) is characterised by left atrial and consequent mitral annular dilatation causing mitral regurgitation. AFMR is likely to become more common with population ageing, alongside increases in atrial fibrillation and heart failure with preserved ejection fraction; conditions causing atrial dilatation. Here, we aim to define the prevalence and characterise the patient and survival characteristics of AFMR in the National Echocardiographic Database of Australia (NEDA). Methods and results: 14 004 adults with moderate or severe FMR were identified from NEDA. AFMR or ventricular FMR (VFMR) was classified by LA size, LV size and LVEF. AFMR was found in 40% (n=5562) and VFMR in 60% (n=8442). Compared with VFMR, the AFMR subgroup were significantly older (mean age 78±11 years), with a higher proportion of females and of AF. Participants were followed up for a median of 65 months (IQR 36–116 months). After adjustment for age, sex, AF, and pulmonary hypertension, the prognosis for VFMR was significantly worse than for AFMR (HR 1.57, 95% CI 1.47 to 1.68 for all-cause and 1.73, 95% CI 1.60 to 1.88, p<0.001 for both). After further adjustment for LVEF, mortality rates were similar in VFMR and AFMR patients (HR 0.93, p=NS), though advancing age and pulmonary hypertension remained independently associated with prognosis. Conclusions: AFMR is a common cause of significant functional MR that predominantly affects elderly female patients with AF. Advancing age and pulmonary hypertension independently associated with survival in FMR. Prognosis was better in AFMR compared with VFMR; however, this difference was accounted for by LV systolic impairment and not by MR severity.